2015
DOI: 10.1177/0022034515600157
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell–Soluble Signals Enhance Multilumen Formation in SMG Cell Clusters

Abstract: Saliva plays a major role in maintaining oral health. Patients with salivary hypofunction exhibit difficulty in chewing and swallowing foods, tooth decay, periodontal disease, and microbial infections. At this time, treatments for hyposalivation are limited to medications (e.g., muscarinic receptor agonists: pilocarpine and cevimeline) that induce saliva secretion from residual acinar cells as well as artificial salivary substitutes. Therefore, advancement of restorative treatments is necessary to improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
3
23
1
Order By: Relevance
“…44 Cch (100 µM) induced an increase in [Ca 2+ ] i in Par-C10 cells cultured under all the conditions studied (i.e., FH, SGIYR, RAD, YIGSR, A99 alone and in combination, Figure 5A–F), consistent with results from previous studies using rat parotid gland and Par-C10 cells. 8,20 However, Par-C10 cells cultured on YIGSR-modified FH (Figure 5B,G) displayed a significantly higher increase of [Ca 2+ ] i as compared to unmodified FH (Figure 5A,G) and A99-modified FH (Figure 5C,G). Furthermore, increases of [Ca 2+ ] i in Par-C10 cells on FH containing both YIGSR and A99 peptides (Figure 5D,G) was significantly different from the [Ca 2+ ] i response observed on FH modified with YIGSR alone.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…44 Cch (100 µM) induced an increase in [Ca 2+ ] i in Par-C10 cells cultured under all the conditions studied (i.e., FH, SGIYR, RAD, YIGSR, A99 alone and in combination, Figure 5A–F), consistent with results from previous studies using rat parotid gland and Par-C10 cells. 8,20 However, Par-C10 cells cultured on YIGSR-modified FH (Figure 5B,G) displayed a significantly higher increase of [Ca 2+ ] i as compared to unmodified FH (Figure 5A,G) and A99-modified FH (Figure 5C,G). Furthermore, increases of [Ca 2+ ] i in Par-C10 cells on FH containing both YIGSR and A99 peptides (Figure 5D,G) was significantly different from the [Ca 2+ ] i response observed on FH modified with YIGSR alone.…”
Section: Resultsmentioning
confidence: 93%
“…These results are relevant to both human and mouse studies, as previous studies showed that both of these cell types form 3D salivary cell clusters when grown on different scaffolds, such as Matrigel or L1. 20,42,43 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, laminin was incorporated into the macromer solutions at 0.1 mg/mL due to previous studies highlighting the efficacy of laminin in both salivary gland regeneration and tissue engineering approaches [27,28,5153]. Briefly, SMG sphere cell number was determined using a hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…ZO-1 is expressed in acini, ducts, and inter-glandular endothelial cells from human major salivary glands and mouse submandibular glands 14,39,81 and is also co-localized with claudin-16 at the excretory duct of human major salivary glands. 81 ZO-1 has been used as a marker for salivary gland polarity and differentiation; 110 however, further studies are needed to determine the molecular mechanisms by which ZO-1 modulates TJs in salivary glands.…”
Section: Tight Junction Plaque Proteinsmentioning
confidence: 99%
“…Several recent studies have demonstrated that TJs can be formed from primary salivary in vitro, 110,[116][117][118][119] an advance which can be used to study barrier function of the salivary epithelium in a system that more closely resembles native tissue. Furthermore, the use of knockout mice for the various TJ proteins will also prove useful in determining the role of these proteins for in vivo salivary gland functioning.…”
Section: Models Available To Study Tight Junctions In Salivary Glandsmentioning
confidence: 99%